2022
DOI: 10.1093/rheumatology/keac594
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune activation and hypersensitization of the AT1 and ETA receptors contributes to vascular injury in scleroderma renal crisis

Abstract: Objectives Scleroderma renal crisis (SRC) is a rare vascular complication of systemic sclerosis with substantial risks for end-stage renal disease and premature death. Activating autoantibodies (Abs) targeting the angiotensin II type 1 (AT1R) and the endothelin-1 type A receptor (ETAR) have been identified as predictors for SRC. Here, we sought to determine their pathogenic significance for acute renal vascular injury potentially triggering kidney failure and malignant hypertension. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Hegner et al . [20 ▪ ] showed that the vasocontractile response of endothelial cells to angiotensin II and endothelin-1 (ET-1) was amplified by IgG from SSc patients with SRC through substantial crosstalk between AT1R and ETAR. AT1R and ETAR belong to a family of G-protein coupled receptors (GPCRs), which are now recognized as preferential autoantibody targets in patients with SSc and other autoimmune diseases [21].…”
Section: Vascular Injurymentioning
confidence: 99%
“…Hegner et al . [20 ▪ ] showed that the vasocontractile response of endothelial cells to angiotensin II and endothelin-1 (ET-1) was amplified by IgG from SSc patients with SRC through substantial crosstalk between AT1R and ETAR. AT1R and ETAR belong to a family of G-protein coupled receptors (GPCRs), which are now recognized as preferential autoantibody targets in patients with SSc and other autoimmune diseases [21].…”
Section: Vascular Injurymentioning
confidence: 99%
“…7 Mechanistically, anti-AT 1 R and anti-ET A R Abs not only activate endothelial cells 8 but also elicit contraction in renal resistance arteries. 9 Importantly, we found evidence that Abs targeting the AT 1 R and the ET A R hypersensitize the receptors to their natural ligands angiotensin II (Ang II) and ET-1. 9 This might facilitate the excessive vasoconstriction found in SRC and enhance the vicious cycle of vascular injury, reduced renal blood supply, and RAAS activation.…”
Section: Introductionmentioning
confidence: 89%
“…Protein-DNA complexes were analyzed by electrophoresis in 6% non-denaturing polyacrylamide gels and visualized with LightShift Chemiluminescent EMSA Kit (Thermo). The activity of NFkB and NFAT signaling was analyzed with EMSA and luciferase assays, respectively, as described previously ( 50 , 51 ).…”
Section: Methodsmentioning
confidence: 99%
“…(A, B) Effect of KTx-IgG on TNF-α protein release from HMECs (A) Upon a 24-hour incubation with 1.0 mg/ml Con-IgG or KTx-IgG from patients with or without vasculopathy or baseline control (pg/ml, n=3 each) and (B) Upon a 24-hour stimulation with 1 mg/ml KTx-IgG from patients with vasculopathy (n=5 each) in the presence or absence of the following stimuli: a) mitogen phorbol-myristate-acetate (PMA, concentration 50 ng/ml), b) thrombin (0.1 U/ml), and c) PAR-1 inhibitor (BMS200261, 1 µM); and (C, D) Analysis of NFkB and NFAT activation in response to KTx-IgG from patients with vasculopathy compared to Con-IgG (each 1 mg/ml for 24 hours). The activity of NFkB and NFAT signaling was analyzed with EMSA and luciferase assays, respectively, as described previously ( 50 , 51 ). The data were analyzed with repeated ANOVA and expressed as Mean +/- SD with *P<0.05, **P<0.01, and ***P<0.001.…”
Section: Supplementary Materialsmentioning
confidence: 99%